QUALIFICATION CLAUSE OF SERIOUS INJURY AND/OR THREATEN TO CAUSE INJURY FOR ENFORCEMENT MECHANISM AS A SAFEGUARD MEASURES UNDER ARTICLE XIX OF GATT 1994 IN POSITIVE LAW INDONESIA - Nyoman Indra Juarsa (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Indonesia is a country that is incorporated within the World Trade Organization or often called the World Trade Organization (WTO) is a multilateral trade accommodate the interests of the countries in the world with backgrounds different economy. Indonesia is known as developing countries are given the opportunity by the WTO to make exceptions to some aspects of the multilateral trading with the aim to make adjustments to trade with other countries. Indicator of a nation 's economy can see in balance Import and Export, for Indonesia influx of imported products from other countries to the domestic market in Indonesia, making domestic manufacturersÂ that produce similar goods and competition will experience losses if the government is not capable of implementing policies to protect domestic product in the country of imported products. Existing security measures to protect domestic product losses is to perform safeguards measures as efforts to protect domestic products from imported products. To be able to file a safety measure needs to be qualified when a product is imported suffered serious losses and the threat of serious injury to be more specifically described in -depth analysis.Keywords : Serious injury, threaten to cause injury, safeguards measures.